2017
DOI: 10.3171/2016.9.jns16431
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin receptor is crucial for glioma development via the Wnt/β-catenin signaling pathway

Abstract: OBJECTIVE The (pro)renin receptor (PRR) plays an essential role in the early development of the central nervous system by activating the Wnt/β-catenin signaling pathway. The authors investigated the potential role of the PRR in the pathogenesis of glioma. METHODS The authors performed immunohistochemical analysis to detect both the PRR and isocitrate dehydrogenase 1 with mutations involving arginine 132 ( IDH1) in paraffin sections of 31 gliomas. Expression of the PRR and Wnt pathway components in cultured hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 45 publications
(52 reference statements)
2
49
1
Order By: Relevance
“…Based on this evidence, further studies convincingly revealed that (P) RR promotes pancreatic [11], brain [13] and colorectal [10] cancers through the Wnt/β-catenin pathway. Interestingly, research also suggests that (P) RR not only serves as a membrane adaptor protein but also exists in the cytoplasm and positively affects the protein expression level of Wnt2 in glioma cells [13] as well as that of Wnt3 and total LRP6 in CRC cells [10]. In summary, (P) RR is a potential novel onco-protein in Wnt/β-catenin pathway-related oncogenesis (Fig.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Based on this evidence, further studies convincingly revealed that (P) RR promotes pancreatic [11], brain [13] and colorectal [10] cancers through the Wnt/β-catenin pathway. Interestingly, research also suggests that (P) RR not only serves as a membrane adaptor protein but also exists in the cytoplasm and positively affects the protein expression level of Wnt2 in glioma cells [13] as well as that of Wnt3 and total LRP6 in CRC cells [10]. In summary, (P) RR is a potential novel onco-protein in Wnt/β-catenin pathway-related oncogenesis (Fig.…”
mentioning
confidence: 83%
“…Kouchi et al [13] reported that aberrant (P) RR overexpression was observed in WHO grade II-IV gliomas independent of IDH1 R132H mutation. Moreover, by detecting the tissue samples of 31 patients, they found that the (P) RR expression level was positively correlated with the WHO grade and Ki-67 labelling index (r = 0.8080, P < 0.0001), and negatively associated with the glioma patients' survival times (r = − 0.6499, P < 0.0002) [13]. At the cellular level, (P) RR promoted the proliferation of human glioma cells through the Wnt/β-catenin pathway and inhibited cell apoptosis by attenuating caspase-3 activation [13].…”
Section: Gliomamentioning
confidence: 99%
See 3 more Smart Citations